ON THE STABILITY OF A GENERAL ADDITIVE FUNCTIONAL INEQUALITY IN BANACH SPACES - Chung, Sang-Cho (Journal of the Chungcheong Mathematical Society, 2013)
In this paper, we prove the generalized Hyers-Ulam stability of the additive functional inequality∥f(2x1) + f(2x2) + … + f(2xn)∥≤ ∥tf(x1 + x2 + … + xn)∥ in Banach spaces where a positive integer n ≥ 3 and a real number t such that 2 ≤ t < n. KCI Citation Count: 1